2015
DOI: 10.1063/1.4908109
|View full text |Cite
|
Sign up to set email alerts
|

Integrability criterion in terms of coprime property for the discrete Toda equation

Abstract: We reformulate the singularity confinement, which is one of the most famous integrability criteria for discrete equations, in terms of the algebraic properties of the general terms of the discrete Toda equation. We show that the coprime property, which has been introduced in our previous paper as one of the integrability criteria, is appropriately formulated and proved for the discrete Toda equation. We study three types of boundary conditions (semi-infinite, molecule, periodic) for the discrete Toda equation,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…However, x 8 and x 9 are co-prime with each other, which leads to a contradiction. In the same manner, we conclude that x 9 must not be a factor of x 10 . Therefore x 10 is irreducible, and is trivially not a unit.…”
Section: Proof Of Theorem 22supporting
confidence: 62%
See 1 more Smart Citation
“…However, x 8 and x 9 are co-prime with each other, which leads to a contradiction. In the same manner, we conclude that x 9 must not be a factor of x 10 . Therefore x 10 is irreducible, and is trivially not a unit.…”
Section: Proof Of Theorem 22supporting
confidence: 62%
“…The coprimeness of the discrete KdV equation was formulated and proved in [9]. In [10], Mada and two of the authors investigated initial value dependence of the discrete Toda lattice equation with several boundary conditions, and showed that the discrete Toda lattice has the coprimeness property. In the subsequent paper [11], we introduced an extension of the bilinear two-dimensional discrete Toda equation:…”
Section: Definition 11mentioning
confidence: 99%
“…and the relation (11). Let us denote the exponent of p ′ n−j (0 ≤ j ≤ n) in the numerator p n as I n−j .…”
Section: Lemmamentioning
confidence: 99%
“…The irreducibility and co-primeness are found out to be useful in formulating the integrability of discrete equations defined over the lattice of dimension more than one. For example, we have proved that these two properties can also be formulated for the discrete Toda equation (both the τ -function form and the nonlinear form) with various boundary conditions: i.e., open, the Dirichlet, and the periodic boundaries [13].…”
Section: Introductionmentioning
confidence: 95%